Extrapleural solitary fibrous tumor of the thyroid gland: A case report and review of literature - Suh, Yong Joon (World J Clin Cases, 2020)
BACKGROUND: Solitary fibrous tumor (SFT) is an uncommon mesenchymal neoplasm that arises from the pleura. A few SFTs have also been described in extrapleural sites. However, SFT of the thyroid gland is rare. Here, we report a case of extrapleural SFT on the thyroid gland, in addition to a literature review. CASE SUMMARY: A 59-year-old man visited our hospital in July 2017 complaining of a large mass in his neck. His thyroid function test results, including antibody levels, were within the normal limits. Ultrasonography showed a 4.7 cm × 4.0 cm × 3.2 cm solitary mass of intermediate suspicion in the left thyroid lobe. A fine-needle aspiration biopsy was subsequently performed. The pathologist reported a benign follicular lesion. However, the size of this nodule increased to 5.5 cm × 5.0 cm × 3.4 cm by April 2018. After a multidisciplinary discussion, a left lobectomy was performed in May 2018. The specimen showed a well-demarcated, partly encapsulated, soft nodule of whitish and tan/brown color on the cut surface. Light microscopy revealed high cellularity with moderate cytologic atypia. The mitotic count was 5/10 high-power fields. There was no tumor necrosis or lymphovascular invasion. The tumor was CD34-positive and signal transducer and activator of transcription 6-positive. Neither thyroid transcription factor-1 nor cytokeratin expression was detected. The Ki-67 showed intermediate proliferative activity. The final diagnosis was extrapleural SFT of the thyroid gland with a clear resection margin. The patient was discharged without complication three days after the surgery. CONCLUSION: In the literature, extrapleural SFT of the thyroid gland has been reported to behave indolently with the capacity for recurrence and rare metastasis, although surgical resection is the treatment of choice. Understanding this disease entity is important for accurate diagnosis and proper management.